Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Menggunakan Media Flashcard Digital pada Siswa Sekolah Dasar - Sidiasih, Nyoman; Sudiana, I Nyoman; Putrayasa, Ida Bagus (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose - Based on the results of observations at SD Negeri 22 Dangin Puri through interviews with several teachers at the nearest elementary school, namely SD Negeri 29 Dangin Puri on October 23, 2023. Various problems faced by grade 2 teachers in learning were found. One of them is the lack of ability to make sentences for class 2 students. This results in low student learning outcomes in writing sentences in Indonesian language subjects. The results of interviews with teachers stated that teachers had never used digital teaching aids in learning to write Indonesian in grade 2. This research aims to develop digital flashcard learning media to improve Indonesian writing learning outcomes for grade 2 elementary school students. Method - This research uses research development (R&D) or development research and uses the Borg and Gall model which consists of 10 stages. This learning media was validated by 4 experts, namely 2 media experts and 2 material experts. This research involved 60 students as research subjects.Findings - The result is that this learning media is very valid, with a validity coefficient of 1. Practicality and effectiveness tests were carried out in field tests. The results of the practicality test show that digital flashcard media is categorized as very practical, both from the teacher and student sides. The results of the effectiveness test show that digital flashcard media is categorized as effective, with an N-Gain of 0.8.Research Implications - The media developed is visual media, namely images displayed on slides designed according to students' material needs. The images are colorful and attractive to students. The media developed in the form of digital flashcards is suitable for use as learning media in elementary schools because this learning media is very valid. The media developed in the form of digital flashcards are suitable for use as learning media in elementary schools because they help students understand the material and help teachers convey the material. In developing learning media, it is based on student needs.